Axial compressive behaviours of square CFST stub columns at low temperatures. (January 2020) - Yan, Jia-Bao; Dong, Xin; Wang, Tao
Abstract: This paper evaluates the low-temperature compressive behaviours of square CFST stub columns (SCFST-SCs) in steel-concrete composite structures. 21 compressive tests were firstly performed on 14 SCFST-SCs and seven rectangular CFST stub columns (RCFST-SCs) at low temperatures of 20, -30,  −60, and −80 °C. The key parameters in this testing program are low temperatures, wall-thickness of steel tube, and shape of the cross section. Concrete crushing, outward local buckling of steel tube, and tensile fracture at the corner of steel tube were three observed failure modes in the compressive tests. The SCFST-SCs and RCFST-SCs exhibited linear, elasto-plastic, and recession working stages. The test results showed that the ultimate compressive resistance and initial stiffness were increased, but the ductility was decreased for the square CFST stub columns as the temperature decreases from 20 to −80 °C. The wall-thickness of steel tube showed equivalent contributions on the improvements of ultimate compressive resistance due to different low temperature, but its influences on ductility tends to be weakened as temperature decreases. Modified Eurocode 4 code equations have been proposed for the predictions on ultimate compressive resistances of SCFST-SCs at low temperatures, and their accuracies were checked by 21 reported test results. Highlights: Low temperature improves stiffness and strength of SCFST/RCFST columns. Low temperature reduces ductility of square/rectangular CFST columns. Improvements of tube-wall thickness on strength of CFST are reduced as temperature decreases. Proposed equations predict well ultimate strength of SCFST/RCFST at low temperature.